Tackling the Infrastructure Challenge in Indonesia - Pisu, Mauro (OECD Economics Department Working Papers, 2010)
Indonesia.s infrastructure is in poor shape, having suffered from protracted under-investment since the Asian financial crisis of the late 1990s, and constraints growth potential. This paper focuses on the current state of the regulatory framework and discusses different options for improvement in order to attract needed private investment. It recognises the ambitious reforms undertaken by the government thus far, but suggests that further efforts are needed. The authorities should establish a simple regulatory environment based on effective regulatory agencies resulting in lower regulatory uncertainty and realign prices to cost-recovery levels. This Working Paper relates to the 2010 OECD Economic Review of Indonesia (www.oecd.org/eco/surveys/Indonesia)